The child psychotherapy treatment planner - Jongsma, Arthur E., Jr., 1943- (Practice planners., 2014)
Treatment plan components for 35 behaviorally based presenting problemsOver 1,000 prewritten treatment goals, objectives, and interventions-plus space to record your own treatment plan optionsA step-by-step guide to writing treatment plans that meet the requirements of most accrediting bodies, insurance companies, and third-party payorsIncludes new Evidence-Based Practice Interventions as required by many public funding sources and private insurers PracticePlanners The Bestselling treatment planning system for mental health profes.